Virtual Reality In Training Impact On Students Of Educational Programs In Augmented Reality (Journal of Pharmaceutical Negative Results, 2023)
Currently, the article is relevant, because virtual reality and augmented reality are our future. This is the latest direction in the use of computers. The article reveals the relationship of a person with the computer world he created, that is, the relationship of the real with the virtual. Technologies, peripheral devices of virtual and augmented reality and their application in various fields are considered. Currently, there is an increasing interest in modern technologies in education, and for a quality learning process, the use of virtual reality technology is considered purposeful. Already in Azerbaijan, in the field of education, as a pilot project, a "3D" classroom was created, where lessons were held in 6-9 grades in biology, zoology and human beings. With the help of virtual technology - "3D" glasses and a special board, students studied the structure, organs and various information about humans, animals and plants [12]. Should this activity be expanded? Create educational programs in augmented reality? How will classes conducted in the virtual world affect pupils and students? The article discusses these issues and reveals the significance and prospects for using modern augmented reality technologies for teaching in the school curriculum.